Cellular Recognition of Mycobacterium tuberculosis ESAT-6 and KatG Peptides in Systemic Sarcoidosis - Drake, Wonder P. (American Society for Microbiology, 2007)
Sarcoidosis is an enigmatic disease with a pathology similar to that of tuberculosis. We detected Th-1 immune responses to Mycobacterium tuberculosis ESAT-6 and KatG peptides from peripheral blood mononuclear cells from 15/26 sarcoidosis, 1/24 purified-protein-derivative-negative (PPD−) (P < 0.0001, Fisher's exact test), and 7/8 PPD-positive (PPD+) subjects (P = 0.21). This finding provides immunologic links between mycobacteria and systemic sarcoidosis.